2022
DOI: 10.3166/rmp-2022-0151
|View full text |Cite
|
Sign up to set email alerts
|

Statut à la naissance et prise en charge des nouveau-nés dans une maternité de dernier recours en Guinée

Abstract: L’analyse du statut et de la prise en charge des nouveau-nés à la maternité d’Ignace-Deen de Conakry (Guinée) à travers cette étude a révélé 8,2 % d’enfants mort-nés, 14,1 % de faible poids de naissance, 10,6 % de macrosomes, 9,3 % de prématurés, 6,8 % d’asphyxie néonatale et 0,3 % de malformations. Environ 24,5 % des nouveau-nés ont eu un score d’Apgar inférieur à 7/10 à la première minute de vie, et 26 % ont eu besoin d’une réanimation à la naissance qui a été réalisée avec succès dans 96,9 % des cas. Enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Takamte Kamgang RR, in his work on the evaluation of the care of the newborn in the delivery room and during the first week of life in Niamey, notes a live birth frequency of 68.8%, i.e., 31.2% of stillbirth [6]. Diallo et al, in Conakry observed a stillbirth rate of 8.2% [7] and Mkoko et al, in Brazzaville a rate of 19 deaths per 1000 live births [8]. The neonatal death rate was 0.5% in 5 months in Yaoundé according to Chelo et al, [9].…”
Section: Prevalence Of Stillbirthsmentioning
confidence: 99%
“…Takamte Kamgang RR, in his work on the evaluation of the care of the newborn in the delivery room and during the first week of life in Niamey, notes a live birth frequency of 68.8%, i.e., 31.2% of stillbirth [6]. Diallo et al, in Conakry observed a stillbirth rate of 8.2% [7] and Mkoko et al, in Brazzaville a rate of 19 deaths per 1000 live births [8]. The neonatal death rate was 0.5% in 5 months in Yaoundé according to Chelo et al, [9].…”
Section: Prevalence Of Stillbirthsmentioning
confidence: 99%